Human health risk assessment of arsenic and potentially toxic elements exposure in bread and wheat flour in Northeast Iran - Fateme Asadi Touranlou; Sajjad Ghasemi; Mahdi Gholian Aval; Mohammad Hashemi; Seyedeh Belin Tavakoly Sany (PLoS ONE, 2025)
Background Bread, a staple food, is at risk of contamination from heavy metals that pose significant health hazards. This study aimed to assess the levels of heavy metals, including Cu, Zn, Fe, Al, Co, As, Hg, Cr, Ni, Pb, Cd, and V, in bread samples collected from bakeries in Mashhad, Iran, and to evaluate the associated health and carcinogenic risks. Methods In this study, the urban area was divided into five regions using simple random sampling. A total of 270 samples, including flour, dough, and bread, were collected from bakeries between June and December 2020. After preparing the samples and applying an acid digestion method, the concentration of heavy metals were determined using an inductively coupled plasma optical emission spectrometer. Results Levels of Al, As, Cr, and Fe exceeded WHO and FAO thresholds in all regions. The health risk assessment indicated that non-carcinogenic risks from arsenic and the mean hazard index for bread consumption exceeded 1 in both adults and children, suggesting potential health risks. Moreover, carcinogenic risk indices for both age groups surpassed the acceptable limit (CR > 1 × 10−4) across all regions, indicating potential carcinogenic effects. Conclusion The findings reveal significant health and carcinogenic risks linked to bread consumption in Mashhad. Continuous monitoring of heavy metal levels in wheat and related food products is recommended to protect public health.